Motivations, media dependency and parasocial interaction: key drivers of SNS active participation - Silvia Sanz-Blas; Daniela Buzova, Daniela Buzova; Victor Ballester-Riera; Paula Fierro-Rubio (JOINETECH, 2025)
Objective and significance of the study – This study aims to understand the psychological and social mechanisms that drive active participation in Social Networking Sites (SNSs). By integrating the Uses and Gratifications Theory, Media Dependency Theory, and Parasocial Interaction, it explores how user motivations, dependency on SNSs, and interactions with other users jointly influence engagement levels in digital platforms.Methodology – An empirical study was conducted with a sample of 904 SNS users in Spain. The research model was tested using Partial Least Squares Structural Equation Modelling (PLS-SEM) to analyse the direct and mediating relationships among the key constructs.Findings – The results show that user motivations are a strong predictor of SNS dependency, which in turn enhances parasocial interaction and active participation. In addition, user motivations and parasocial interaction with other users significantly reinforce behavioural engagement. These findings confirm the multidimensional nature of SNS use, shaped not only by functional needs but also by emotional and social bonds.Study limitations – The generalisability of the results may be limited due to the specific geographic context (Spain) and the cross-sectional design.Practical value of the findings – The study offers a validated, theory-based framework that helps platform developers, marketers, and community managers understand the psychological drivers of user participation. The insights can support strategies aimed at fostering user engagement, enhancing content relevance, and strengthening loyalty through emotional and social connection.
Keywords: Social Networking Sites (SNS); Uses and Gratifications Theory; Media Dependency Theory; Parasocial Interaction; Active Participation.